An evaluation of fatigue factors in maritime pilot work scheduling. (2nd October 2020) - Gregory, Kevin; Hobbs, Alan; Parke, Bonny; Bathurst, Nicholas; Pradhan, Sean; Flynn-Evans, Erin
ABSTRACT: Maritime piloting operations involve on-call work schedules that may lead to sleep loss and circadian misalignment. Our study documented pilot work scheduling practices (n = 61) over a one-year period. Most pilots worked a week-on/week-off schedule. Work periods averaged 7.6 hours in duration and pilots worked up to four ship assignments during a given work period. Work weeks averaged a total of 35.0 hours with pilots working on average three consecutive days. Night work was common (19.0 hours/week) with 02:00 h the most common starting hour for a work period. On-call work periods occurred at irregular times with a high degree of start time variability between consecutive work periods. While typical individual and weekly work total hours were not high, there were instances with long work periods, minimal rest opportunities, and extended total weekly work hours. Fatigue-model predictions based on work schedules were similar to objective outcomes collected among other groups of maritime pilots and may prove useful in identifying potential fatigue risks within on-call work schedules. Future studies should be conducted using objective measures to provide further insight on how on-call maritime operations influence sleep timing, alertness, and performance.